Incidencia de la cultura tributaria en la recaudación del impuesto predial en la Municipalidad Provincial de Ucayali - Contamana, 2021 - Gratelly García, Sol Anggi (2022)
The thesis presented aimed to determine the incidence of tax culture in the collection of property tax in the Provincial Municipality of Ucayali Contamana, 2021, was inclined to a study of applied type, correlational level and non-experimental design, including as study population 371 taxpayers, the survey was used as a technique and as an instrument the questionnaire. After analyzing the results, it was determined that the tax culture is rated as average (28%), since sometimes it has knowledge about taxes to fulfill its obligations; likewise, it has sometimes been motivated to comply with the payment of taxes, in addition, that the government sometimes informs the destination that is given to the collection of taxes; on the other hand, the collection of property tax the highest percentage was 36% where it is evident that it has achieved a remarkable compliance by taxpayers. To conclude, the incidence of tax culture in the collection of property tax in the Provincial Municipality of Ucayali Contamana is significant, with a correlation coefficient of 0.807 and a significance of 0.000.